ANALISIS HUKUM PENGENAAN BEA MASUK ANTIDUMPING PRODUK KERTAS TERTENTU INDONESIA DI KOREA - , Antini Triwidati, SH, Dina w. kariodimedjo S.H.,LLM. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
If it proves detrimental dumping the importing country then the country can apply additional import duty of a product called anti-dumping tariffs Extra Duties or antidumping duties (BMAD) in products containing dumping. Sanctions, however, is normal for the imposition of dumping anti-dumping duties. Antidumping duty can not exceed the fixed antidumping margins, antidumping duties only held for long periods of time and so far it is necessary to neutralize the dumping which in this case caused the loss. Based on this background, the purpose of this study was to understand the dispute over the imposition of antidumping duties of certain paper products in Korea and Indonesia what steps are taken by the Government relating to this dispute and finally to analyze the issues behind Indonesia sued Korea to the WTO DSB panel . This study uses normative juridical approach that is based on library research to obtain secondary data. Addition of field research was also conducted to obtain primary data through interviews of respondents and other sources. The results show that there are some outstanding issues behind Indonesia Korea sued to the WTO DSB that the Panel used the principle of "Facts Available" in the calculation of dumping margins by reason of the three companies (PT Indah Kiat, PT Pindo Deli and PT Tjiwi Chemistry) incorporated in Sinar Mas Group / SMG did not co-operative.Indonesiaassumedin thiscase theKTCviolatedthe provisions ofArticle6.8 andAnnexII of theantidumpingAgreement( ADA)because itviolatesthe provisionsregarding the use ofdata"Best Information Available"